Challenging boardroom homogeneity : corporate law, governance, and diversity - Dhir, Aaron, 1975- (Cambridge University Press, 2015)
"Drawing on semi-structured interviews with corporate board directors in Norway and documentary content analysis of corporate securities filings in the United States, Challenging Boardroom Homogeneity empirically investigates two distinct regulatory models designed to address diversity in the boardroom: quotas and disclosure. The author's study of the Norwegian quota model demonstrates the important role diversity can play in enhancing the quality of corporate governance, while also revealing the challenges diversity mandates pose. His analysis of the US regime shows how a disclosure model has led corporations to establish a vocabulary of 'diversity'. At the same time, the analysis highlights the downsides of affording firms too much discretion in defining that concept. This book deepens ongoing policy conversations and offers new insights into the role law can play in reshaping the gendered dynamics of corporate governance cultures"--